WORKSHOP MENGGAMBAR DENGAN CHARCOAL DI CUSH CUSH GALLERY DENPASAR - I Gede Jaya Putra (LPPM Institut Desain dan Bisnis Bali, 2020)
This journal discusses the drawing workshop using charcoal techniques and materials. Based on observations in the field, many children who still do not understand themselves related to the creativity that can be produced. Children are a very free phase, full of honesty, passionate and brave in doing actions that are able to express themselves. However, there are several factors that cause many expressions of children to not surface. Expressions related to emotions and feelings lead to one understanding, namely art. One type of art that is able to bring out the expression of children is drawing. Drawing has many techniques, one of which is by using charcoal as a way of expressing it. So drawing with charcoal is used as a workshop approach for children, as a means to understand themselves and bring out their creativity. Workshop activities initiated by the Cush Cush gallery and again Bali were held on July 13, 2019 at the Cush Cush gallery, aimed at educating children, providing awareness of art, to understanding life and making art as a provision for the future, in taking on the work world its orientation on creative people. Keyword : Charcoal, Creativity, Drawing, Expression, Workshop.